El padre Coloma y su novela pequeñeces. Noticia breve acerca de algunos personajes - Serna Galindo, Ricardo (2013)
This paper is aimed at writing down some defining features of the characters that play a key role in the novel Pequeñeces written by Father Luis Coloma. In that work several plots are developed in parallel, and one of them concerns Freemasonry directly. We stress the importance of that plot because in such storylines all that is unique and mysterious can be found in this Jesuits’ entertaining novel.